The fungal expel of 5-fluorocytosine derived fluoropyrimidines mitigates its antifungal activity and generates a cytotoxic environment. - Luis Enrique Sastré-Velásquez; Alex Dallemulle; Alexander Kühbacher; Clara Baldin; Laura Alcazar-Fuoli; Anna Niedrig; Christoph Müller; Fabio Gsaller (PLoS Pathogens)
Invasive aspergillosis remains one of the most devastating fungal diseases and is predominantly linked to infections caused by the opportunistic human mold pathogen Aspergillus fumigatus. Major treatment regimens for the disease comprise the administration of antifungals belonging to the azole, polyene and echinocandin drug class. The prodrug 5-fluorocytosine (5FC), which is the only representative of a fourth class, the nucleobase analogs, shows unsatisfactory in vitro activities and is barely used for the treatment of aspergillosis. The main route of 5FC activation in A. fumigatus comprises its deamination into 5-fluorouracil (5FU) by FcyA, which is followed by Uprt-mediated 5FU phosphoribosylation into 5-fluorouridine monophosphate (5FUMP). In this study, we characterized and examined the role of a metabolic bypass that generates this nucleotide via 5-fluorouridine (5FUR) through uridine phosphorylase and uridine kinase activities. Resistance profiling of mutants lacking distinct pyrimidine salvage activities suggested a minor contribution of the alternative route in 5FUMP formation. We further analyzed the contribution of drug efflux in 5FC tolerance and found that A. fumigatus cells exposed to 5FC reduce intracellular fluoropyrimidine levels through their export into the environment. This release, which was particularly high in mutants lacking Uprt, generates a toxic environment for cytosine deaminase lacking mutants as well as mammalian cells. Employing the broad-spectrum fungal efflux pump inhibitor clorgyline, we demonstrate synergistic properties of this compound in combination with 5FC, 5FU as well as 5FUR.